Equitable Substance Use Treatment for Migrants and Ethnic Minorities in Flanders, Belgium: Service Coordinator and Expert Perspectives - Charlotte De Kock (SAGE Publishing, 2022)
Despite mounting evidence of disparities in health service provision for migrants and ethnic minorities (MEM) across EU countries, there has been limited research into how services (meso) and policy (macro) can contribute to reducing these disparities. In Flemish (Belgian) substance use treatment (SUT) policy making, no systematic attention is given to MEM. Nevertheless, preliminary studies have identified some disparities, especially among non-Belgian MEM. For this paper we studied the factors related to these disparities and ways forward based on 21 semi-structured interviews with SUT coordinators and experts. The low representation of MEM populations in psychiatric hospitals due to language exclusion criteria stands out as the main disparity. Moreover, respondents indicated that exclusion may be anticipated by general practitioners in the referral process, causing additional disparities. The exclusion of MEM from policy making processes, waiting lists and the structure of the federalized Belgian health system are identified as indirect macro contributors to disparities. Respondents specified four main ways to reduce disparities in SUT among MEM: targeted treatment and policy making, installing diversity policies in SUT services, enhancing training and education, and community-based treatment.